Implementasi ajaran Sariswara pada ekstrakurikuler menari di SD Negeri Cokrokusuman - Febriyanto, Rizki Lutfi Rima; Indriyanti, Poppy; Aulia, Fauziah; Damayanti, Refiana Eka Asita; Qhoiriyatun, Putri; Nurani, Dana Kusuma (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This research aims to explore how Sariswara's teachings are implemented in dance extracurricular activities at Cokrokusuman State Elementary School as an effort to enrich students' learning experiences and strengthen cultural and spiritual values ​​in education. A qualitative approach was used with data collection techniques through participant observation, interviews and document analysis. The findings show that the integration of Sariswara's teachings has enriched the dance learning context by introducing philosophical elements and cultural values ​​in every movement and choreography. In addition, the implementation of Sariswara's teachings has increased students' understanding of the harmony between body, mind and spirit, as well as increased their appreciation of cultural diversity and artistic expression. This research contributes to our understanding of the role of traditional teaching in improving the quality of arts education at the primary level